Overexpression of vacuolar H+-pyrophosphatase from a recretohalophyte Reaumuria trigyna enhances vegetative growth and salt tolerance in transgenic Arabidopsis thaliana - Li, Ningning; Cui, Yuzhu; Zhang, Zijian; Wang, Shuai; Sun, Yaqing; Zhang, Shaoying; Li, Guolong (Frontiers in Plant Science, 2024)
Reaumuria trigyna is an endangered recretohalophyte and a small archaic feral shrub endemic to the arid and semiarid plateau regions of Inner Mongolia, China. Based on transcriptomic data, we isolated an H + -pyrophosphatase gene from R. trigyna (RtVP1) that encoded a plasma membrane and tonoplast-localized protein. RtVP1 was rapidly upregulated by NaCl and exogenous abscisic acid treatment and rescued the sucrose-sensitive deficiencies of the AtVP1 mutant (avp1). Transgenic Arabidopsis overexpressing RtVP1 exhibited a higher leaf area, plant height, root length, fresh weight, and soluble carbohydrate accumulation compared to the wild type (WT) under normal conditions.RtVP1 overexpression increased the seed germination rate and decreased the reduction rate of root length, fresh weight, and chlorophyll content in transgenic plants under salt stress. Catalase enzyme activity, proline content, relative water content, and soluble sugar content increased significantly in salt-stressed transgenic Arabidopsis plants, whereas the malondialdehyde content decreased significantly. Transgenic Arabidopsis accumulated more K + and less Na + in its leaves and had a lower Na + /K + ratio than WT. In transgenic Arabidopsis roots, K + was unchanged, but Na + and the Na + /K + ratios were reduced compared to WT. When RtVP1 was expressed in the AXT3 yeast strain, the accumulation of Na + and K + in the intracellular increased, and the Na + /K + ratio decreased. These results show that R. trigyna RtVP1 promotes the vegetative growth of plants, mainly by regulating carbohydrate metabolism, and confers salt tolerance in transgenic Arabidopsis by maintaining Na + /K + homeostasis and enhancing the osmotic and antioxidant regulatory capacity. These results suggest that RtVP1 may be a good target for improving crop yield and salt tolerance.